Concept of Samanya Vishesha Siddhanta & its Utility in Ayurveda: Review - Chavda, Komalben; Prajapat, Monika; Sharma, Ashok Kumar; Sharma, Kishori Lal; Meena, Rekh Raj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda places great emphasis on prevention and encourages the maintenance of health through close attention to balance in one’s life, right thinking, diet, lifestyle and the use of medicine. In ayurveda there are many number of Siddhanta like, Panchmahabhuta Siddhanta, Triguna Siddhanta and Samanya Vishesha Siddhanta etc. which form a strong foundation for the survival of this life science. The Samanya Vishesha Siddhanta is one such basic principle of ayurveda, which helps to treat disease. Samanya Means Similarity and Vishesha means Dissimilarity. These are widely described and implemented in Charaka Samhita and are mentioned under Six Factors required for the action of Dhatusamya in the body. An effort has been made to comprehend Charaka Samhita in the Utility of Samanya Vishesha Siddhanta in this study.